(untitled) (Medico Legal Update, 2019)
Adverse drug reactions (ADR) are happen more frequently based on different drugs. ADR should be monitored by Pharmacovigilance. Due to drug usage of single dose or combine dose ADR are happen. ADR can’t be monitored in INDIA because of not follow the physician direction and also self-medication. Most of the Indians used drug store or online to purchase drugs. The proposed method utilised different websites and online drugs reviews with sentiment analysis and conjugate gradient method in neural network. In output, we propose the best way to monitor the ADR and drug harmfulness.